2007
DOI: 10.1007/s11666-007-9080-1
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Kinetics of Plasma-Sprayed Zirconia TBCs

Abstract: A model of the sintering exhibited by EB-PVD TBCs, based on the principles of free energy minimization, was recently published by Hutchinson et al [1]. In the current paper, this approach is applied to the sintering of plasma-sprayed TBCs and comparisons are made with experimental results. Predictions of through-thickness shrinkage and changing pore surface area are compared with experimental data obtained by dilatometry and BET analysis respectively. The sensitivity of the predictions to initial pore architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The spraying conditions, and coating microstructures, were similar to those reported elsewhere [31,[75][76][77]. The predictions shown were obtained using input data, and predictions from the sintering model, shown in Table I.…”
Section: Overall Conduction Through Tbcs -The "Two Flux Regimes" Analsupporting
confidence: 55%
See 1 more Smart Citation
“…The spraying conditions, and coating microstructures, were similar to those reported elsewhere [31,[75][76][77]. The predictions shown were obtained using input data, and predictions from the sintering model, shown in Table I.…”
Section: Overall Conduction Through Tbcs -The "Two Flux Regimes" Analsupporting
confidence: 55%
“…It's also clear that these changes lead to increases in (effective) thermal conductivity (and also in stiffness). Since the sintering model of Cipitria et al [76,77,85] is based on much the same geometrical model as that of Golosnoy et al [15] for prediction of conductivity, and also involves similar microstructural characterisation parameters, it's possible to combine them in order to predict how the conductivity changes during heat treatment. For example, Fig.9 compares such predictions with experimental data from Ratzer-Scheibe et al [73,74], relating to PS YSZ TBCs given short or prolonged heat treatments at 1100˚C.…”
Section: Predicted Changes In Conductivitymentioning
confidence: 99%
“…Recently, Cipitria et al have proposed a numerical analysis model for sintering in free-standing plasma-sprayed coatings [16,17]. Hence, we discussed the relevance between the obtained differences in shrinkage behavior and the microstructure by using this numerical model.…”
Section: Resultsmentioning
confidence: 89%
“…The quartic Runge-Kutta method was utilized to solve Eq. (3), in which the required material properties for the calculation were referred to Cipitria's report [16].…”
Section: Resultsmentioning
confidence: 99%
“…They found the surface area of cracks and voids kept decreasing beyond 600°C and almost 33% of surface area of voids and microcracks have been lost from as sprayed coating to 1000°C heat‐treated coating. There are various other studies which have shown the effect of sintering on reduction in porosity content and volume shrinkage …”
Section: Introductionmentioning
confidence: 99%